Rice breeding for higher crop productivity (a review) - G. L. Zelensky; O. V. Zelenskaya (Труды по прикладной ботанике, генетике и селекции)
The main global trends in the breeding of rice cultivars and hybrids are higher plant productivity, adaptability to cultivation conditions, quality of products, and resistance to environmental stressors, including diseases.Efforts of leading breeding centers in the Philippines and China to further increase the rice yield are associated with a change in the plant morphotype: shorter plants with erectoid leaves and large panicles with a high number of grains.The International Rice Research Institute (IRRI) has developed rice cultivars that under favorable conditions in the tropical zone produce a grain yield of up to 10–11 t/ha, with Kecon = 0.5. A heterotic hybrid of rice was obtained in China with a yield of 13.9 t/ha; it has a new plant morphotype (New Plant Type) and a growing season of 163 days. The hybrid is classified as “super rice”.Modern breeding programs are aimed at producing cultivars of “Green Super Rice” using pedigree methods and backcrossing for introgression of target genes through DNA markers, QTL mapping, pyramiding, and recurrent selection.Russian breeders have traditionally produced rice cultivars adapted to local conditions, with a growing season of no more than 125 days. In the 1980s, a program was launched to develop a high-yielding rice cultivar with erectoid leaves for condensed planting. As a result of multiple stepwise hybridization and targeted selection, new source material with target traits of “super rice” was released. Cv. ‘Polyus-5’ with a new plant morphotype was obtained on its basis. This cultivar was included in the State Register and from 2023 approved for commercial production. During the field trials, ‘Polyus-5’ yielded a maximum of 1380 g/m2 over 120 days of the growing season, under the conditions of condensed sowing and increased mineral nutrition.